Structural conditioning and mediation by student agency : a case study of success in chemical engineerng design - Kotta, Linda Thokozile (Department of Chemical Engineering, 2015)
The study, informed by Bhaskar’s realist philosophy for social science, seeks to provide an explanation for the differential success rates in a final year chemical engineering design course.